Evaluación ergonómica en el área de producción en la empresa DISPOSTES CÍA. LTDA. - Castellano Tarco, Thalía Gissel (2020)
DISPOSTES Cia. Ltda. Is a company that is dedicated to the production and sale of Street lights, it is locatedin San Buenaventura neighborhood, Latacunga City, Cotopaxi Province, its processes and its function involves all kind of risks. In the production area, the identification and evaluation of ergonomic risks was carried out using the INSHT matrix where a qualitative evaluation of the risks found was obtained, the NORDIC questionnaire was applied where data on the inconvenience of workers who work in that area was showed the following health problems such as pains in the neck (27%), shoulder (33%), dorsal or lumbar (27%), elbow or forearm (27%) and wrist or hand (33%) which are attributed to the work, ergonomic evaluation methods known nationally and internationally as RULA and NIOSH. Taking into account the forced postures and lifting weisht that workers perform during their workday, thus determining the leve lof risk and intervention which help to minimize ergonomic risk and in turn skeletal muscle disorders. The project is applyed for forced postures where the elaboration of a procedure of active pauses that contains exercises of joint mobility and muscular stretching, for lifting weights the elaboration of a procedure of prevention of lifting weishts, in addition to their respective socialization to all workers, to perform the work in a safer possible way, avoiding suffering skeletal muscle disorders such as neck injuries, example cervical tension syndrome, shoulder injuries, example shoulder tendonitis, elbow injuries, example round pronator syndrome, wrist injuries, example syndrome of the carpal tunnel and hand and finger injuries example white finger syndrome.